Deletion of Neuropilin 1 from Microglia or Bone Marrow–Derived Macrophages Slows Glioma Progression - Jeremy Tetsuo Miyauchi; Michael D. Caponegro; Danling Chen; Matthew K. Choi; Melvin Li; Stella E. Tsirka (2017)
Abstract Glioma-associated microglia and macrophages (GAM), which infiltrate high-grade gilomas, constitute a major cellular component of these lesions. GAM behavior is influenced by tumor-derived cytokines that suppress initial antitumorigenic properties, causing them to support tumor growth and to convert and suppress adaptive immune responses to the tumor. Mice that lack the transmembrane receptor neuropilin-1 (Nrp1), which modulates GAM immune polarization, exhibit a decrease in glioma volumes and neoangiogenesis and an increase in antitumorigenic GAM infiltrate. Here we show that replacing the peripheral macrophage populations of wild-type mice with Nrp1-depleted bone marrow-derived macrophages (BMDM) confers resistance to the development of glioma. This resistance occurred in a similar fashion seen in mice in which all macrophages lacked Nrp1 expression. Tumors had decreased volumes, decreased vascularity, increased CTL infiltrate, and Nrp1-depleted BMDM adopted a more antitumorigenic phenotype relative to wild-type GAMs within the tumors. Mice with Nrp1-deficient microglia and wild-type peripheral macrophages showed resistance to glioma development and had higher microglial infiltrate than mice with wild-type GAMs. Our findings show how manipulating Nrp1 in either peripheral macrophages or microglia reprograms their phenotype and their pathogenic roles in tumor neovascularization and immunosuppression. Significance: This study highlights the proangiogenic receptor neuropilin 1 in macrophages and microglial cells in gliomas as a pivotal modifier of tumor neovascularization and immunosuppression, strengthening emerging evidence of the functional coordination of these two fundamental traits of cancer. Cancer Res; 78(3); 685–94. ©2017 AACR.